Clavicular fracture in a collegiate football player: A case report of rapid return to play - Rabe, S. B.; Oliver, G. D. (Journal of Athletic Training, 2011)
Objective: To present the case of surgical treatment and rehabilitation of a midshaft clavicular fracture in a National Collegiate Athletic Association Division I football athlete.